2005
DOI: 10.1159/000081782
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Manifestations of Multiple Myeloma

Abstract: Purpose: To describe ophthalmic manifestations in a series of patients with multiple myeloma (MM) and review the literature. Design: Retrospective case series. Methods: Review of all cases with ophthalmic manifestations of MM seen at the Department of Ophthalmology, Royal Adelaide Hospital, between 1987 and 2002. Results: Of all patients with MM who were managed at the Royal Adelaide Hospital in the study period, only 8 were referred to the Ophthalmology Department with ophthalmic manifestations. Five males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 36 publications
0
44
0
4
Order By: Relevance
“…It affects many organ systems and typically presents with bone lesions, anaemia, hypercalcemia, kidney disease, bone marrow failure and various infections (Turaka 2014;Fung et al 2005). Neoplastic plasma cell tumours arising in soft tissues without primary osseus involvement is normally known as primary extramedullary plasmacytoma (Aboud et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It affects many organ systems and typically presents with bone lesions, anaemia, hypercalcemia, kidney disease, bone marrow failure and various infections (Turaka 2014;Fung et al 2005). Neoplastic plasma cell tumours arising in soft tissues without primary osseus involvement is normally known as primary extramedullary plasmacytoma (Aboud et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Among the ocular complications, corneal involvement is less well recognized than others. 7 Precise epidemiologic studies on the prevalence of corneal involvement in monoclonal gammopathies are not available; data from Bourne et al 37 showed a prevalence of one case out of 100 gammopathic patients, while in a prospective study, Aronson and Shaw 38 detected no corneal deposits in 13 patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, MM is a malignant plasma cell disorder characterized by excess BM plasma cells, monoclonal protein, osteolytic bone lesions, renal disease, anemia, and hypercalcemia. 1,2 The eye can be involved in monoclonal gammopathies as a consequence of the ophthalmic localization, 3 blood hyperviscosity, 4,5 or deposition of light chains in the ocular tissues. 6 Among the ocular localizations, corneal involvement is the less well recognized than others.…”
mentioning
confidence: 99%
“…1,2 Whilst ocular involvement in chronic GVHD (cGVHD) is a frequent complication after alloHSCT, 3 ocular involvement by multiple myeloma is rare. 4 Here, we report a case of a 42-year-old male patient who presented with isolated orbital relapse of multiple myeloma during treatment of severe ocular cGVHD. He received alloHSCT from a gender-and HLA-matched sibling PBSC donor after conditioning with treosulfan and fludarabin as primary treatment for multiple myeloma (IgA-kappa) in partial remission after autologous HSCT in August 2007.…”
mentioning
confidence: 96%
“…They can be the result of direct tissue infiltration by plasma cells or from increased blood viscosity. 4 Orbital involvement as an indicator of extramedullary recurrence of multiple myeloma in patients thought to be in remission is an exceptional case. 5 Common symptoms of orbital involvement by multiple myeloma are proptosis, decreased vision, diplopia, swelling and ptosis.…”
mentioning
confidence: 99%